Indication of Resuscitative Endovascular Balloon Occlusion of the Aorta in Non-Traumatic Hemorrhage - Shinozuka, Ken; Aoki, Makoto; Ishida, Kenichiro; Maruhashi, Takaaki; Matsumura, Yosuke (Journal of Endovascular Resuscitation and Trauma Management, 2022)
Many blunt trauma injuries have multiple bleeding points and are accompanied by coagulopathy. In contrast, in a non-traumatic injury, the patient often demonstrates a single bleeding site that is rarely accompanied by coagulopathy. Thus, resuscitative endovascular balloon occlusion of the aorta (REBOA) is considered more effective in non-traumatic cases than in traumatic cases. In addition, in non-traumatic cases, REBOA may be used for central blood flow control during definitive hemostasis and prevention of expected massive bleeding. In such cases, REBOA should be used carefully to avoid complications. We describe the indications for and uses of REBOA in non-traumatic cases based on existing evidence.